2019
DOI: 10.1088/1361-6560/ab0145
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of CT ventilation imaging and hyperpolarised gas MRI: effects of breathing manoeuvre

Abstract: Image registration of lung CT images acquired at different inflation levels has been proposed as a surrogate method to map lung 'ventilation'. Prior to clinical use, it is important to understand how this technique compares with direct ventilation imaging modalities such as hyperpolarised gas MRI. However, variations in lung inflation level have been shown to affect regional ventilation distributions. Therefore, the aim of this study was to evaluate the impact of lung inflation levels when comparing CT ventila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 49 publications
0
12
0
Order By: Relevance
“…This might also be explained with the comparison of a static ventilation image acquired after a single inhalation of 129 Xe with a dynamic examination of tidal breathing using PREFUL‐MRI. It has been shown that the extent of VDP (and the reproducibility of measurements as well) with hyperpolarized gas depends on the chosen gas, the inflation state (ie, chosen breathing maneuver and applied gas volume 36 ) and the latency between inhalation and scan allowing gas uptake in delayed‐filling lung regions; for example, via collateral ventilation 37 . Kirby et al observed visually and quantitatively higher VDP obtained with 129 Xe MR imaging in comparison to 3 He MR imaging in patients with COPD but not in healthy subjects, 38 and Obert et al measured higher VDP using 19 F in comparison to 129 Xe 39 .…”
Section: Discussionmentioning
confidence: 99%
“…This might also be explained with the comparison of a static ventilation image acquired after a single inhalation of 129 Xe with a dynamic examination of tidal breathing using PREFUL‐MRI. It has been shown that the extent of VDP (and the reproducibility of measurements as well) with hyperpolarized gas depends on the chosen gas, the inflation state (ie, chosen breathing maneuver and applied gas volume 36 ) and the latency between inhalation and scan allowing gas uptake in delayed‐filling lung regions; for example, via collateral ventilation 37 . Kirby et al observed visually and quantitatively higher VDP obtained with 129 Xe MR imaging in comparison to 3 He MR imaging in patients with COPD but not in healthy subjects, 38 and Obert et al measured higher VDP using 19 F in comparison to 129 Xe 39 .…”
Section: Discussionmentioning
confidence: 99%
“…Positive (or negative) values of indicate local lung volume expansion (or contraction) during inspiration, which is used as a surrogate for ventilation. Prior studies have shown that CTVI has good regional accuracy with Galligas PET [ 19 ] and hyperpolarized gas MRI [ 20 ], and has been incorporated to guide functional-avoidance planning [ 8 , 13 15 ].…”
Section: Methodsmentioning
confidence: 99%
“… 66 Ventilation assessment using tissue expansion metrics based on the deformation fields generated by DIR or the differences in tissue density between the coregistered image pairs have shown reasonable correlation with the regional assessment of ventilation using Xenon CT 48,67 and Xenon-MRI. 68 However, variability between registration approaches has led to a poor correlation between DIR-based ventilation metrics and reference modalities at the voxel level. 69 …”
Section: Ai In Functional Quantificationmentioning
confidence: 99%